Transnationalism and Sri Lanka's migrant housemaids : the kitchen spoon's handle - Gamburd, Michele Ruth 1965- (New Delhi : Vistaar Publications, 2002)
On the alien labor influx from Sri Lanka to the Persian Gulf Region; a study.
Includes bibliographical references (p. [251]-265) and index.
Keywords: Foreign workers, Sri Lankan -- Persian Gulf Region; Women foreign workers -- Persian Gulf Region; Employment in foreign countries -- Sri Lanka; Transnationalism